Hemingway i Gellhorn - Stahl, Jerry 1954-; Kidman, Nicole 1967-; Strathairn, David 1949-; Owen, Clive 1964-; Shalhoub, Tony 1953-; Posey, Parker 1968-; Ulrich, Lars 1963-; Parker, Molly 1972-; Santoro, Rodrigo 1975- (Warner Home Video, 2013)
Tells the story of the passionate love affair and tumultuous marriage between Martha Gellhorn and Ernest Hemingway, following the adventurous writers through all the great conflicts of their time
Polnische DVD-Ausgabe
Title from container
Orig.: USA, 2012
Special feature: audio commentary by Philip Kaufman and Walter Murch
Keywords: Biografischer Film; Fernsehfilm; Gellhorn, Martha / 1908-1998 / Drama; Hemingway, Ernest / 1899-1961 / Drama; Man-woman relationships / Drama; Gellhorn, Martha / 1908-1998; Hemingway, Ernest / 1899-1961; Man-woman relationships; Relaciones hombre-mujer / Drama; Drama films; Feature films (E-H); DR.; Biographical films; Drama; Feature films; Fiction films; Film; DVD-Video